THE EVOLUTION OF ENGLISH SPEAKING INSTRUCTION: A COMPARISON OF DIGITAL AND TRADITIONAL METHODS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This paper explores the evolution of English speaking instruction by examining both traditional teaching methods and digital tools. The study provides an in-depth comparison between the conventional classroom-based approaches, including face-to face interaction, role-playing, and drills, and modern digital methods, such as language learning apps, online platforms, and virtual reality.